Gambaran Regulasi Emosi pada Mahasiswa yang Mengalami Kecemasan Sosial - Nurlina; Selian, Sri Nurhayati (Indo Publishing, 2025)
College students often face academic and social demands that can trigger social anxiety, making emotion regulation an essential component of their psychological well-being. This study aims to describe students’ experiences in regulating their emotions when dealing with social anxiety, identify the strategies they use, and analyze the factors influencing their emotional regulation processes. This research employed a qualitative phenomenological approach with three participants selected through purposive and snowball sampling. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman’s model consisting of data reduction, data display, and conclusion drawing. The findings indicate that students frequently use emotion regulation strategies such as avoidance, emotional suppression, and cognitive reappraisal, influenced by previous social experiences, environmental support, and emotional self-efficacy. The study concludes that social anxiety shapes a complex dynamic of emotional regulation, where students often struggle between expressing their emotions and avoiding negative evaluation. The novelty of this study lies in its in-depth exploration of students’ subjective emotional experiences, which remains underexplored in previous quantitative research. The implications highlight the need for culturally sensitive and context-based campus interventions to help students develop more adaptive emotion regulation strategies.